PENGARUH PUPUK NPK DAN KOMPOS TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KEDELAI HITAM (Glycine soja (L) Merr.) VARIETAS DETAM 1 - Saroh, Eulis; Tadjudin, E; Sungkawa3, Iman (Agroswagati : Jurnal Agronomi, 2023)
The greater public awareness of fulfilling the needs of vegetable protein and the growing black soybean processing industry, black soybean plants have become one of the staple food crops whose needs continue to increase. However, in fulfilling the people's need for soybeans, the government is still relying on imports from other countries. Black soybean is a staple in the food processing industry, especially as the main ingredient for making soy sauce. To meet the increasing demand for black soybeans, efforts are needed to increase production and productivity, one of which is through effective and efficient fertilization. The purpose of this study was to determine the effect of NPK fertilizer and compost on the growth and yield of black soybean plants (Glycine soja (L) Merr) variety detam 1, to determine the best results from NPK and compost fertilizer treatment and to determine the relationship between growth components and yield components of the black soybean plant (Glycine Soja (L) Merr) variety Detam 1. The experiment was carried out at the Al-Zaytun Islamic Boarding School Experimental Garden which is located in Mekarjaya Village, Gantar District, Indramayu Regency, West Java. The method used was a randomized block design (RBD) with the following treatments: A (25 kg/ha NPK fertilizer and 8 tons/ha compost), B (25 kg/ha NPK fertilizer and 10 tons/ha compost), C (25 NPK fertilizer kg/ha and compost 12 tonnes/ha), D (NPK fertilizer 50 kg/ha and compost 8 tonnes/ha), E (NPK fertilizer 25 kg/ha and compost 10 tonnes/ha), F (NPK fertilizer 50 kg/ha) ha and compost 12 tonnes/ha), G (NPK fertilizer 75 kg/ha and compost 8 tonnes/ha), H (NPK fertilizer 75 kg/ha and compost 10 tonnes/ha) and I (NPK fertilizer 25 kg/ha and compost 12 tonnes/ha). There was a significantly different effect on NPK and compost treatment on plant height observations of 14 HST, 21 HST and 28 HST, number of leaves 14 HST, 21 HST and 28 HST, leaf area index 21 HST and 28 HST, root volume at 14 HST, 21 HST and 28 HST, Growth rates 14-21 HST and 21-28 HST, number of filled pods, number of empty pods, and seed weight per plot. The highest yield of soybeans occurred in treatment E (NPK 50 kg/ha and compost 10 tons/ha) with a dry soybean seed value of 1.22 kg/plot or the equivalent of 2.03 tons/ha and when converted to 80% optimal land 1 .63 tonnes/ha. There is a significant relationship in the observation of the number of leaves aged 14, 21 and 28 DAP, root volume aged 14, 21 and 28 DAP